Percepción de los docentes de la Unidad Educativa Alfredo Pérez Guerrero sobre la educación no presencial de emergencia mediadas por las TIC. - Paredes Llamuca, Amanda Marcela (2023)
The main objective of this research work is to know the perception of teachers in the Unidad Educativa Alfredo Pérez Guerrero of the Guano canton, about the usefulness no presential emergency education mediated by TIC during the Covid 19 pandemic. quantitative approach with non-experimental design. Using a 40-item questionnaire, considering as a sample 38 teachers who were working in the school year September 2021 - July 2022. In relation to the perception that teachers have through the results obtained, it was evidenced that they prefer presential, because the participation of students is forced only based on a grade. In addition, some teachers found it difficult to use the distance education methodology, however, according to their opinion, their performance as a teacher was not affected by the students, since the implementation of TIC tools facilitated the process. This is how it was possible to identify that the TIC tools they used were: Google Drive in 52.6%, Google Classroom 39.5%, Educaplay 28.9% and in others with 36.8% in which they mentioned Microsoft Teams and Zoom as one of the most effective alternatives according to the survey results.